Discussion on the Practice of Expatriate Employees in Cross Culture of Subsidiaries – Taking Wal-Mart as an Example - Shen, Jiayi (Transactions on Economics, Business and Management Research, 2024)
Wal-Mart has a large number of subsidiaries around the world and is relatively well staffed, but due to various factors, its revenue contribution to overseas business is relatively low. This illustrates Wal-Mart’s prospects and obstacles in the international market. The enterprise’s foreign workers encounter new demands and obstacles as the degree of internationalization is continuously improved. Dispatched employees are the core of connecting the headquarters and subsidiaries of multinational companies and play an important bridge role. Therefore, the cross-cultural practice discussion of expatriated employees has become a focus of international human resources management at present. This article will explore the cultural differences faced by Wal-Mart in the process of communication between expatriate employees sent by the headquarters to each subsidiary and the host country in 2015-2024 through the retrieval and qualitative analysis of literature, and explore these cross-cultural problems. The study investigate a number of real-world solutions to examine a range of cross-cultural issues that Wal-Mart employees face in the host country.